Jute fabric in the development of a smart thermochromic textile - Ana Paula Hiller; André Luiz Marquardt; Andrea Cristiane Krause Bierhalz; Fernanda Steffens (The Journal of Engineering and Exact Sciences)
In recent years, the market has shown a growing interest in adding value to textile materials through the search for natural processes that are less harmful to the environment. In this context, the use of natural fibers from plants provides very attractive properties, such as biodegradability, UV protection, acoustic insulation, among others. In this way, the purpose of this work was to functionalize a fabric from jute fiber with a thermochromic agent, making it a material with an intelligent property, being able to react thermally to the environment in which it is inserted. Through the analysis of reflectance spectrophotometry, the L*, a* and b* coordinates of the targeted and functionalized tissues were observed. When the ?E of the samples functionalized at 4 different points was analyzed, good homogeneity of the thermochromic agent in the tissue was verified. The aging effect of the thermochromic agent was evaluated on the tissue for 1, 15 and 30 days after functionalization, where a slight increase in the b* value was observed, which indicates a certain loss of blue coloration in the sample. It was verified, therefore, that the functionalized jute fabric presented satisfactory results, allowing its use in other areas of application, mainly when referring to the interaction with the environment in which it is inserted.